Pengembangan E-LKPD Berbasis Attention, Relevance, Confidence, and Satisfaction (ARCS) Menggunakan Liveworksheets Pada Materi Kesetimbangan Kimia Di Kelas XI SMA/MA Sederajat - Hasanah, Fien; Rasmiwetti, Rasmiwetti; Susilawati, Susilawati (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
This study aims to develop an Electronic Student Worksheet (E-LKPD) based on the ARCS motivational model (Attention, Relevance, Confidence, Satisfaction) using the Liveworksheets platform, focusing on the topic of chemical equilibrium for grade XI senior high school students. The research was motivated by the low student motivation and learning outcomes resulting from the use of conventional, less interactive worksheets. The method employed was Research and Development (R&D) using the ADDIE model, which includes five stages: Analyze, Design, Develop, Implement, and Evaluate. The product was developed through a series of needs analyses, prototype designs, expert validations, and limited user trials involving teachers and students. Validation results indicated that the ARCS-based E-LKPD achieved an average score of 97.42% for content validation and 97.22% for media validation, both categorized as very valid. User trials showed very positive responses from teachers (96.56%) and students (91.06%). Therefore, the developed E-LKPD is deemed appropriate as an innovative teaching material capable of enhancing student motivation, conceptual understanding, and the effectiveness of chemistry learning.